Dilema Subaltern Syi’ah Sampang: Sebuah Studi Awal - Ali, Fiqh Vredian Aulia (LoroNG: Media Pengkajian Sosial Budaya, 2015)
Social religious and political context of the vulnerable sectarian in Sampang Regency make adherents of Shia Sampang hasn’t been able to return to hometown. It has been two years of age the relocation of displaced Shia Sampang, assault and intimidation experienced by their. The relocation policy on behalf of the protection of the safety of Shia followers of Sampang, often quite inconsistent with the indication security protection as their desired as a community represented. However, the idea of a reconciliation team, social scientists and activists to return the refugees Shiah Sampang revolutionary to hometown, is not congruent with not conducive atmosphere, full of intimidation and there is no guarantee of safety in the hometown. Konteks sosial keagamaan dan politik yang rentan sektarian di Kabupaten Sampang membuat para penganut Syiah Sampang belum dapat kembali ke kampung halaman hingga kini. Telah dua tahun usia relokasi pengungsi Syi’ah Sampang, pasca penyerangan dan intimidasi yang dialami mereka. Kebijakan relokasi yang mengatasnamakan perlindungan keselamatan penganut Syi’ah Sampang, seringkali justru tidak sejalan dengan pembayangan perlindungan keamanan sebagaimana diinginkan mereka sebagai komunitas yang direpresentasi. Akan tetapi, gagasan tim rekonsiliasi, aktivis dan ilmuan sosial untuk mengembalikan pengungsi Sy’iah Sampang secara revolusioner ke kampung halaman, tidak sebangun dengan suasana yang nirkondusif, penuh intimidasi dan tidak ada jaminan keselamatan di kampung halaman.